STRATEGI STORYNOMICS DALAM PENGEMBANGAN DAYA TARIK WISATA BUDAYA DI KEPULAUAN SELAYAR - Lisani, Nur (Universitas Hasanuddin, 2024)
Storynomics, a marketing strategy, has been adapted for managing tourist destinations, particularly in the Selayar Islands. This strategy emphasizes the power of storytelling to influence emotions and produce economic benefits. Despite the challenges of reviving tourism after the pandemic, strategies can be implemented to promote tourist attractions and activities through storytelling. Selayar, a marine-based destination known for its famous attractions, can also incorporate cultural heritage through storytelling strategies. This study will use a qualitative method and descriptive data analysis to explore the potential of cultural and historical tourism resources in the Selayar Islands, the potential of applying storynomics strategies, and the approach to applying storynomics strategies based on the island's character. The results are expected to serve as an example for other areas and serve as a basis for applied research to help manage tourist attractions in Indonesia. Keywords: storynomics, tourist destination, cultural tourism, marine tourism, marine cultural.